Bilateral vertebral artery dissection complicated by posterior circulation stroke in a young man: A case report. Issue 44 (30th October 2020) - Li, Zhichao; Liu, Junni; Wang, Xiang; Liu, Xiaohui; Sun, Qinjian; Du, Yifeng; Yin, Ling
Abstract: Introduction: Vertebral artery dissection (VAD) is a common cause of stroke in young and mid-aged adults without predisposing risk factors for vascular disease. It can be induced by a particular head or neck posture; its early signs often include headache and neck pain. Improved imaging techniques can be used to detect VAD, whose current treatment options are limited. Patient concerns: The patient presented with neck and shoulder pain for a week after sleeping against the wall with cervical proneness for 1 night. He had sudden headache, slurred speech, and left side weakness for 1.5 hours on admission. Diagnosis: The patient had VAD complicated by posterior circulation stroke. Interventions: Acute stroke was treated with intravenous thrombolytic therapy. Then, the patient was administered follow-up anticoagulants. Outcomes: The patient's condition improved after thrombolytic therapy. He recovered well, with no recurrence during a 4-year follow-up. Conclusion: VAD should be taken into consideration in differential diagnosis of posterior circulation stroke or transient ischemic attack in young patients. Intravenous thrombolytic therapy may be safe and effective for stroke-complicated cases. This case report demonstrates that expanded diagnostic protocol for acute ischemic stroke assures rapid and correct diagnosis.